2019
DOI: 10.3390/molecules24203745
|View full text |Cite
|
Sign up to set email alerts
|

The Disturbance of Hepatic and Serous Lipids in Aristolochic Acid Ι Induced Rats for Hepatotoxicity Using Lipidomics Approach

Abstract: Aristolochic acid I (AAI) was regarded as the major toxic component of aristolochic acid (AA). In addition to aristolochic acid nephropathy (AAN), liver cancers induced by AAI has aroused increasing attention recently. In this paper, the discovery of diagnostic biomarkers for AAI-induced liver injury has been studied, especially for the lipid markers. From the histopathological characteristics, the injury was observed clearly in the liver apart from the kidney after 30 mg/kg of AAΙ treatment for one week, whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…We measured AST, ALT and TBIL to evaluate the degree of liver injury, but there was no significant change in either neonatal or adult mice. Similarly, one study reflected that AST or ALT decreased to the level of the control group on the 14th day after oral- administration of 30 mg/kg AAI in male SD rats (Zhou et al, 2019). The findings suggested that liver cells were damaged in the early stage and may be repaired in the later stage.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…We measured AST, ALT and TBIL to evaluate the degree of liver injury, but there was no significant change in either neonatal or adult mice. Similarly, one study reflected that AST or ALT decreased to the level of the control group on the 14th day after oral- administration of 30 mg/kg AAI in male SD rats (Zhou et al, 2019). The findings suggested that liver cells were damaged in the early stage and may be repaired in the later stage.…”
Section: Discussionmentioning
confidence: 90%
“…Then, in the AAI-treated neonatal mice, AAI disturbed the phospholipid metabolic process and promoted arachidonic acid metabolism to release inflammatory factors. A previous study revealed that phospholipase A2 (PLA2) is responsible for catalyzing phosphatidylcholine transfer to hemolytic lecithin, accompanied by the release of arachidonic acid and fatty acids (Zhou et al, 2019). In the metabolic pathway, phosphatidylcholine was converted into LysoPC (22:4 (7Z, 10Z, 13Z, 16Z)/0:0) (by 1.9735-fold) and arachidonic acid to generate leukotriene D4 (LD4) (by 3.4274-fold).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, the present results indicate that AA-I can cause an increase in the liver index and the elevation of serum GOT and GPT, which is in accordance with the results from Yeh et al’s study in 2008 [ 36 ]. It has been reported that AA-I can induce diffuse hepatocyte swelling and vacuolar degeneration in rats [ 37 ]. Similarly, the current result of histopathological changes indicated that AA-I caused hepatocyte injury in a dose-dependent manner and the histopathological changes are characterized by obvious hepatocyte swelling, vesicular degeneration and steatosis.…”
Section: Discussionmentioning
confidence: 99%